2021
DOI: 10.1186/s13550-021-00766-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of contouring methods on pre-treatment and post-treatment dosimetry for the prediction of tumor control and survival in HCC patients treated with selective internal radiation therapy

Abstract: Introduction The aim of this study was to evaluate the impact of the contouring methods on dose metrics and their predictive value on tumor control and survival, in both situations of pre-treatment and post-treatment dosimetry, for patients with advanced HCC treated with SIRT. Methods Forty-eight patients who underwent SIRT between 2012 and 2020 were retrospectively included in this study. Target volumes were delineated using two methods: MRI-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Specifically concerning 90 Y-loaded resin microspheres, a threshold of 100-120 Gy as a predictor of treatment response or OS has been identified by several studies [27]. In this context, therefore, the cutoff reported in the cohort of patients investigated in this study was in agreement with other authors [7,[28][29][30].…”
Section: Dose-survival Relationshipsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically concerning 90 Y-loaded resin microspheres, a threshold of 100-120 Gy as a predictor of treatment response or OS has been identified by several studies [27]. In this context, therefore, the cutoff reported in the cohort of patients investigated in this study was in agreement with other authors [7,[28][29][30].…”
Section: Dose-survival Relationshipsupporting
confidence: 89%
“…Moreover, Nodari et al [7] reported a cutoff in terms of the target mean absorbed dose of 115 and 98 Gy, using 99m Tc-MAA SPECT/CT-and 90 Y PET/CT-based dosimetry, respectively, for predicting the OS.…”
Section: Dose-survival Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Nodari et al . used a multi-modality deformable registration algorithm in MIM SurePlan (v7.0.1; MIM software Cleveland, USA), performed by a trained medical physicist, to register the liver tumor contours from MR images to 99m Tc-MAA-SPECT/CT and 90 Y-PET/CT [ 19 ]. Their study indicates that different tumor contours from anatomical and scintigraphic images have no significant impact on mean dose, and registering anatomical tumor contours to scintigraphic images is feasible for improving therapeutic strategy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…used a multi-modality deformable registration algorithm in MIM SurePlan (v7.0.1; MIM software Cleveland, USA), performed by a trained medical physicist, to register the liver tumor contours from MR images to 99m Tc-MAA-SPECT/CT and 90 Y-PET/CT [ 19 ]. Their study indicates that different tumor contours from anatomical and scintigraphic images have no significant impact on mean dose, and registering anatomical tumor contours to scintigraphic images is feasible for improving therapeutic strategy [ 19 ]. Besides, our in-house non-rigid liver registration regularized by a spring model was applied in our previous studies on the development of pre-treatment dosimetry [ 6 ] and evaluation of the predictive value of 99m Tc-MAA-based dose planning [ 20 ].…”
Section: Introductionmentioning
confidence: 99%